Penerimaan Masyarakat Surabaya terhadap Citra Politik Tri Rismaharini Pasca Pemberitaan Sujud di Kaki Guru SLB di Youtube KOMPASTV - Rusdiansyah, Alvin Akmal Ramadhan; Febriyanti, Syafrida Nurrachmi (Jurnal Ilmiah Wahana Pendidikan, 2023)
The video's timeline starts on February 21, 2023, when Tri Rismaharini visited the Pajajaran SLB for business. Local people and teachers of Pajajaran SLB were present to welcome the Minister of Social Affairs when she arrived. This commitment was made to her nickname, Risma, by a number of her professors. The promised land is still being used for other people with impairments, hence this bill has not been implemented. In the video, Risma expressed regret when describing to several Pajajaran SLB instructors the chronological order of the challenges encountered in realizing the land grant. Stuart Hall's technique to reception analysis is applied in the descriptive qualitative research methodology. Purposive sampling was employed by the researcher to select 5 informants for interviews who satisfied the three criteria for Stuart Hall's theoretical standpoint. The authors discovered that Tri Rismaharini had previously performed the act of prostrating in other Kompas TV videos based on the findings of the study and debate. One could see public prostration as a way to show reverence for a higher power, such as God, a religious leader, a prominent politician, or another strong person. In this circumstance, prostration is seen as a display of deference, submission, or acceptance of one's position of power.